Urgensi Pemahaman Makna Proklamasi Untuk Siswa Sekolah Dasar Dalam Kehidupan Sehari-Hari - Anisa Nurhasanah; Nishfa Syahira Azima; Tin Rustini (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
The Proclamation was born when the Indonesian people really hoped to be free from the colonial nation. The Indonesian nation must respect and appreciate the proclamation. The proclamation was born from the sacrifices of Indonesian independence figures and heroes. Over time, the meaning of the proclamation began to become almost unknown in the eyes of the Indonesian people themselves. The nation's next generation must understand the meaning of the proclamation itself. After understanding the meaning of the proclamation, implementing an attitude that emulates the proclamation will be appropriate. This research was studied using the literature study method by searching for all sources on the topic of the urgency of understanding the meaning of the proclamation for elementary school students. The aim of this research is to review how important it is for the Indonesian people to understand the meaning of the proclamation starting from an early age. In this way, it is important for every Indonesian citizen to review the importance of understanding the meaning of the proclamation to create and continue sovereignty and maintain Indonesian independence.